Evaluation of seed priming on germination and growth of basil (Ocimum basilicum L. cv. 'Genovese') - Bojović Biljana M.; Kanjevac Milica M.; Todorović Marija S.; Jakovljević Dragana Z. (Kragujevac Journal of Science, 2022)
The priming method is a technique that can greatly improve seed performance and provide high-quality seeds for successful production. In this study, the effect of hormopriming (GA3 and IAA), halopriming (MgSO4 and KNO3), osmopriming (AA, H2O2) and hydropriming (H2O) on the germination, as well as initial stages of growth and development of basil (Ocimum basilicum L. cv. 'Genovese') were investigated. The application of different priming methods not only improved the germination performances of basil, but also significantly influenced the growth of seedlings (root length, shoot length, fresh mass, and vigor index) with the best results achieved by priming with GA3 and H2O2. In addition, it has been found that the concentration of photosynthetic pigments and soluble protein content can be improved by the appropriate priming treatment. The most favorable effect on the examined parameters was achieved during treatment with H2O2.